Strengthening Families: Social and Emotional Competence - David C. Diehl; Jessica Wente; Larry F. Forthun (EDIS, 2011)
Parents foster positive social and emotional development through their everyday interactions with children. This 3-page fact sheet lists some things you can do to support the most positive social and emotional development of your children. Written by David C. Diehl, Jessica Wente, and Larry F. Forthun, and published by the UF Department of Family Youth and Community Sciences, December 2011.